Comprehensive Investigation of the Omega-Shaped Hybrid CFRP Sheet - Concrete Slab System: Experimental, Numerical and Analytical study (Journal of Civil Engineering Researchers, 2023)
Fiber Reinforced Polymer (FRP) composites have been broadly applied in substitution of steel members at rehabilitation interventions thanks to their lightweight, high strength, and high corrosion resistance. Producing novel FRP-concrete hybrid structures is the next step researchers are dealing with. In this context, the present study focuses on the numerical and analytical modeling of the experimentally obtained response of hybrid FRP-concrete slabs subjected to three points bending tests. The analyzed hybrid elements consisted of an omega shape Carbon Reinforced Polymer (CFRP) sheet on which a concrete layer was cast forming a unidirectional slab member. A Glass Fiber Reinforced Polymer (GFRP) fabric was bonded to the CFRP sheet and embedded into the concrete block to provide a connection between CFRP and concrete in one of the specimens. Simulation results showed agreement with the experimental response in terms of load-displacement curve, concrete plastic strain and failure mode. After validating the model, alternative designs (width, height, and thickness of CFRP sheet and concrete block on it) were numerically tested to study the influence of the geometry of the structural system on the load-bearing capacity. Lastly, analytical formulation assuming total compatibility and based on Euler-Bernoulli theory were implemented and contrasted with the experimental response. Overall results pointed out that the optimum design would be the one with increased height of both concrete and CFRP. For this improved configuration, the load-bearing capacity was increased by up to 44%.
Keywords: Hybrid FRP-concrete; Carbon Fiber Reinforced Polymer (CFRP); Numerical model; Flexural behavior; Analytical model